Efeito do anabolizante decanoato de nadrolona na viabilidade, prolifera????o, ades??o e diferencia????o em c??lulas musculares C2C12. - Oliveira, Elisangela Nascimento de (2010)
Studies indicate that the anabolic nandrolone decanoate modulates cell cycle regulation, but little is known about its effects on muscle cells. The aim of this study was to evaluate the effect of anabolic nandrolone decanoate on proliferation, adhesion and differentiation of C2C12 skeletal muscle cells. The cells were cultured in a regular, 10% fetal bovine serum (FBS) and simulation of nutritional deficiency (5% FBS) and incubated with the steroid / vehicle at concentrations of 5, 10, 25 and 50??M. The control group did not receive the treatment. Cell proliferation was assessed in 24, 48 and 72 (short term) and 3 and 5 days (long-term), and the adhesion in 20, 40 and 60 min, using the MTT assay. The myogenic markers expression was assessed after 2, 4 and 8 hours using real time PCR. The results show that nandrolone decanoate did not induce significant changes in cell proliferation in short-term adherence. In the long term after 5 days there was a statistically significant increase in proliferation of cells treated with the anabolic 5??M when cultured in a regular situation and 25??M in simulation of injury, compared with the other concentrations and control. Furthermore, after 8 hours incubation, C2C12 cells showed an increased expression of myogenin in comparison to other periods while MyoD did not change during periods and study groups, no differences between the treated and control groups. Conclusion: The anabolic steroid nandrolone induced an increase in cell proliferation after five days in a dose-dependent but did not interfere in the adhesion and expression of myogenic markers.